2017
DOI: 10.1615/critrevimmunol.2017024944
|View full text |Cite
|
Sign up to set email alerts
|

Lung Injury and Loss of Regulatory T Cells Primes for Lung-Restricted Autoimmunity

Abstract: Lung transplantation is a life-saving therapy for several end-stage lung diseases. However, lung allografts suffer from the lowest survival rate predominantly due to rejection. The pathogenesis of alloimmunity and its role in allograft rejection has been extensively studied and multiple approaches have been described to induce tolerance. However, in the context of lung transplantation, dysregulation of mechanisms, which maintain tolerance against self-antigens, can lead to lung-restricted autoimmunity, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Hence, another hypothesis for the development of pre-existing LRA is that T cells specific for LRA are not eliminated in the thymus, but are rendered inactive by antigen-specific forkhead box P3 (Foxp3)+ regulatory T cells (Tregs) (19)(20)(21)(22)(23)(24). Therefore, loss of Tregs, perhaps due to toxins or infections, could stimulate the expansion of lung tissuerestricted T cells, which in turn could help to break B cell anergy and develop LRA (25)(26)(27). These mechanisms also explain the development of pre-existing LRA in patients candidate for transplantation with end-stage lung disease, such as those with COPD or ILD.…”
Section: Development Of Lra Prior To Transplantmentioning
confidence: 99%
“…Hence, another hypothesis for the development of pre-existing LRA is that T cells specific for LRA are not eliminated in the thymus, but are rendered inactive by antigen-specific forkhead box P3 (Foxp3)+ regulatory T cells (Tregs) (19)(20)(21)(22)(23)(24). Therefore, loss of Tregs, perhaps due to toxins or infections, could stimulate the expansion of lung tissuerestricted T cells, which in turn could help to break B cell anergy and develop LRA (25)(26)(27). These mechanisms also explain the development of pre-existing LRA in patients candidate for transplantation with end-stage lung disease, such as those with COPD or ILD.…”
Section: Development Of Lra Prior To Transplantmentioning
confidence: 99%
“…It has been proposed that the development of anti-tissue-specific Abs after lung transplantation may be produced by a two-hit mechanism. First, the apoptosis of regulatory T cells, which has been shown to occur after viral infections, and second, the exposure of the antigens, which leads to antibody production [75]. An interesting finding is that such antigens, as well as donor HLA antigens, can be found in exosomes both in the serum and bronchoalveolar lavage of lung recipients with ABMR or BOS but not in stable lung recipients [76].…”
Section: Anti-k-alpha 1 Tubulin and Anti-collagen Abs In Lung Transplantationmentioning
confidence: 99%
“…However, during transplantation the self-antigens might be revealed as the structural proteins are cleaved, for example through the activation of matrix metalloproteinases, allowing the preexisting LRAs to bind and promote downstream immune activation ( 13 ). These self-antigens are extravascular but the increased vascular permeability that occurs during ischemia-reperfusion injury could allow extravasation of the LRAs ( 14 ). We found that LRAs compound ischemia-reperfusion injury through the activation of complement, resulting in severe PGD.…”
Section: Introductionmentioning
confidence: 99%